Antitrust Law and Legal Advocacy: Perspective on Promoting Fair Competition in Indonesia, Uzbekistan, and Russia - Dwi Edi Wibowo; Fradhana Putra Disantara; Bazarova Dildora Baxadirovna; Ildar Begishev (Universitas Negeri Semarang, 2026)
Antitrust law plays a critical role in ensuring fair competition, yet its effectiveness varies across different legal and institutional contexts. This paper examines the comparative regulation and implementation of antitrust law in Indonesia, Uzbekistan, and Russia, with particular attention to the role of legal advocacy and legal services in enhancing compliance and enforcement. The objective is to analyze how these three countries, with distinct political and economic systems, construct and operationalize their competition law frameworks to promote healthy market competition. Employing a normative legal research method with a comparative approach, the study relies on statutory texts, institutional documents, case law, and scholarly literature. Data were collected through library research and analyzed qualitatively using descriptive-comparative analysis. The findings reveal that Indonesia has developed a comprehensive legal framework through Law No. 5/1999, yet its enforcement remains inconsistent due to institutional limitations and judicial resistance. Uzbekistan has adopted modern competition principles in its 2012 Competition Law, but enforcement is hindered by state dominance in the economy and limited legal capacity. Russia, in contrast, possesses a mature regulatory framework and a powerful Federal Antimonopoly Service (FAS), though enforcement often reflects political considerations. Across all three contexts, legal advocacy and professional legal services significantly influence compliance by educating businesses, guiding merger notifications, and shaping litigation strategies. This study contributes to comparative competition law scholarship by highlighting the interplay between regulation, enforcement, and advocacy in shaping effective competition regimes. The conclusion underscores that building effective antitrust law requires not only robust statutes but also active advocacy and accessible legal services. Recommendations include strengthening compliance mechanisms in Indonesia through KPPU’s DPKPU guidelines, enhancing legal education in Uzbekistan to foster a bottom-up competition culture, and encouraging FAS Russia to sustain transparency in digital markets.